Synthesis, structure and superoxide dismutase-like activity of two mixed-ligand Cu(II) complexes with N, N′-bis(2-pyridylmethyl)amantadine. (15th October 2016) - Zhou, Ying-Hua; Liu, Xian-Wen; Chen, Li-Qing; Wang, Su-Qing; Cheng, Yong
Graphical Abstract: Two mixed-ligand Cu(II)–amantadine complexes were synthesized and characterized by single crystal X-ray diffraction. Each Cu(II) cation was penta -coordinated with the slightly distorted tetragonal pyramid geometry. Both complexes showed the quasi -reversible Cu(II)/Cu(I) one-electron redox waves determined by the cyclic voltammetry. The frontier molecular orbital energies were calculated by DFT method at B3LYP/LanL2DZ set. The superoxide dismutase like activity (IC50 ) of complex1 and2 were measured to be 0.167 and 0.242 μM, respectively. Abstract: Two mixed-ligand Cu(II) complexes, [Cu(L 1 )(L 2 )](ClO4 )2 ·H2 O (1 ) and [Cu(L 1 )(L 3 )](ClO4 )2 ·H2 O·CH3 OH (2 ) (L 1  =  N, N ′-bis(2-pyridylmethyl)amantadine, L 2  = 5, 5′-dimethy-2, 2′-bipyridine, and L 3  = 1, 10-phenanthroline), were synthesized and characterized by elemental analysis, UV–Vis, infrared spectra and single crystal X-ray diffraction. Copper ions in1 and2 behave the slightly distorted tetragonal pyramid configuration provided by CuN5 coordination set. Both complexes exhibit the quasi -reversible Cu(II)/Cu(I) one-electron redox waves determined by the cyclic voltammetry. Moreover, the frontier molecular orbital energies were obtained by DFT calculations with B3LYP method at LanL2DZ basis. Furthermore, by using NBT assay at pH 7.8, the superoxide dismutase (SOD)-like activity (IC50 ) of1 and2 were measured to be 0.167 and 0.242 μM, respectively. The difference in SOD-like activities of two complexes could be ascribed to the rigidity of the auxiliary ligands.